MENINGKATKAN MINAT BELAJAR ANAK MELALUI BIMBINGAN BELAJAR DENGAN METODE RATA JAM MAINYA (CERAMAH, TANYA JAWAB, BERMAIN DAN BERNYANYI) DI DESA PALASARI - Ayu Sahara Sadar Alimuda; Lutfiyah; Rasmitadila; Fikni Mutiara (Kanigara, 2023)
During the transitional period of the Covid-19 pandemic, it greatly impacted children's interest in learning. The lack of interest in learning felt by children because they are used to learning via mobile phones and full parental assistance is carried out within two years. This condition is used by students of Community Service Program (KKN) to develop a program to fill study time without a teacher with joint learning activities with KKN students. These activities are intended to help children in the Palasari Village environment to gain additional knowledge so as to generate enthusiasm and interest in learning. This activity is a solution to this problem through the Average Jam Play method (lectures, questions and answers, playing and singing). The method approach is through mentoring teaching and learning activities with the help of a descriptive qualitative approach. The success of this tutoring activity is that it can foster the enthusiasm and interest of children in the Palasari Village environment to carry out group learning activities carried out at the KKN post